Biophysical evidence for conformational change in MHC class I molecules upon peptide binding - Springer, S; Poring, K; Townsend, A (1997)
MHC class 1 molecules hind peptides of 8-12 amino acids in the endoplasmic reticulum of mammalian cells to present them at the reil surface to cytotoxic T lymphocytes. In crystal structures of the complex, peptides are deeply buried within a binding groove. We have expressed the murim1 class I molecule H'2Dh in soluble form, complexed with human beta-2 tnicroglobulin, in chinese hamster ovary cells. Purified peptide-free class I complexes are stable at 4 °(-, and are stabilised against thermal denaturation-by the binding of peptide. We have used these complexes to generate complete sets of kinetic association and dissociation as well as equilibrium binding constants of unmodified peptides using tritium labelled peptides and the natural tryptophan fluorescence of the protein. For the peptide FAPGNYPAL, the equilibrium binding constant of 0.2 x U)7 \ll and the kinetic dissociation constant of 7.1 x 10"6 s"1 (at 1 °C') predict a slow association rate, 650 Ms"'. for a simple one-step model of binding. Instead, we find fast association kinetics with 1.1 x 10b Ms"1 by stopped-flow fluorescence spectroscopy. Association is stower if the peptide is longer than optimal, modified by iodination, and also in the presence of detergent. This 'kinetic mismatch' suggests a multi-step binding mecha nism involving a conformational change of the class I binding groove in the poptide binding process. Therefore, the structure of a class I binding site at the time-point of peptide recognition might be different from what is seen in crystaliographic studies.